Sickle cell anemia as a racialized disease: Design principles of a teaching sequence for education about ethnic-racial relations - Meyer Nascimento, Lia Midori; Sepúlveda, Claudia; N. El-Hani, Charbel; Sánchez Arteaga, Juanma (EDeR. Educational Design Research, 2025)
In this paper, we present the results of the first prototyping cycle of an Educational Design Research aiming at the validation of design principles of a Teaching Sequence (TS) on the racialization of sickle cell anemia and its relations with the history of scientific racism. The goal of the TS is to promote education about ethnic-racial relations, health education, and a balanced critical understanding of science in the context of a Biology preservice teacher education course in Brazil. The three design principles investigated in this paper refer to the specific goal of promoting education about ethnic-racial relations in a science teaching context: 1) Approaching the polysemy of the concept of human races; 2) Making a critical examination of sickle cell anemia racialization along history; 3) Addressing the risk of a new eugenics in the genetic counseling process. We tested the TS in 2018, in six meetings with students. In our analyses, we found evidence validating the three investigated design principles. After the formative evaluation of this prototype, we refined the principles and the TS to carry out a new prototyping cycle.